Pembatasan Pekerjaan Dan Dampaknya Pada Karyawan Dengan Keterbatasan Opsi Karier - Yessica Amelia; Grace Yulianti; Sri Utami Nurhasanah (Jurnal Visi Manajemen, 2025)
This study aims to explore the impact of job restrictions on employees with limited career options and the challenges faced by companies in addressing these issues. Using a qualitative literature review, the study found that job restrictions, such as non-compete agreements, can negatively impact employees with limited career options. These impacts include reduced job mobility, career stagnation, and lower income. However, companies can mitigate these effects by implementing fair and transparent policies and providing adequate support to employees. This research highlights the need for balancing corporate resource protection with employee career development to maintain long-term productivity and organizational sustainability.